Simplifique:
por favor me ajudem urgente
Soluções para a tarefa
Respondido por
0
Olá, Zanardereginata.
![\sqrt{( 3^{4}) ^{-\frac{3}{2} }}=\sqrt{3^{4\cdot(-\frac{3}{2})}}=\sqrt{3^{2\cdot(-3) }}=\sqrt{3^{-6}}=3^{\frac{-6}{2}}=3^{-3}=\frac1{3^3}=\frac1{27} \sqrt{( 3^{4}) ^{-\frac{3}{2} }}=\sqrt{3^{4\cdot(-\frac{3}{2})}}=\sqrt{3^{2\cdot(-3) }}=\sqrt{3^{-6}}=3^{\frac{-6}{2}}=3^{-3}=\frac1{3^3}=\frac1{27}](https://tex.z-dn.net/?f=%5Csqrt%7B%28+3%5E%7B4%7D%29+%5E%7B-%5Cfrac%7B3%7D%7B2%7D+%7D%7D%3D%5Csqrt%7B3%5E%7B4%5Ccdot%28-%5Cfrac%7B3%7D%7B2%7D%29%7D%7D%3D%5Csqrt%7B3%5E%7B2%5Ccdot%28-3%29+%7D%7D%3D%5Csqrt%7B3%5E%7B-6%7D%7D%3D3%5E%7B%5Cfrac%7B-6%7D%7B2%7D%7D%3D3%5E%7B-3%7D%3D%5Cfrac1%7B3%5E3%7D%3D%5Cfrac1%7B27%7D)
Perguntas interessantes
Matemática,
1 ano atrás
História,
1 ano atrás
Ed. Física,
1 ano atrás
História,
1 ano atrás
Química,
1 ano atrás